Effects of Semaglutide on Heart Failure Outcomes in Diabetes and Chronic Kidney Disease in the FLOW Trial - Pratley, Richard E.; Tuttle, Katherine R.; Rossing, Peter; Rasmussen, Søren; Perkovic, Vlado; Nielsen, Olav Wendelboe; Mann, Johannes F.E.; MacIsaac, Richard J.; Kosiborod, Mikhail N.; Kamenov, Zdravko; Idorn, Thomas; Hansen, Marco Bo; et al. (Journal of the American College of Cardiology, 2024)
Background: People with type 2 diabetes (T2D) and chronic kidney disease (CKD) are at high risk for heart failure (HF) and premature death from cardiovascular (CV) causes. The FLOW (Research Study To See How Semaglutide Works Compared to Placebo in People With Type 2 Diabetes and Chronic Kidney Disease), which enrolled participants with T2D and CKD, demonstrated that semaglutide, a glucagon-like peptide-1 receptor agonist, reduced the incidence of the primary composite outcome (persistent ≥50% decline in estimated glomerular filtration rate, persistent estimated glomerular filtration rate <15 mL/min/1.73 m2, kidney replacement therapy, and kidney or CV death) by 24%. Objectives: This prespecified analysis examined the effects of semaglutide on HF outcomes in this high-risk population. Methods: Participants were randomized (1:1) to once-weekly subcutaneous semaglutide 1 mg or placebo. The prespecified main outcome was a composite of HF events (new onset or worsening of HF leading to an unscheduled hospital admission or an urgent visit, with initiation of or intensified diuretic/vasoactive therapy) or CV death. HF data were collected by the investigator. CV death was adjudicated by an independent committee. Results: A total of 3,533 randomized participants were followed for a median of 3.4 years. HF was present at baseline in 342 participants (19.4%) in the semaglutide group and 336 (19.0%) in the placebo group. In the overall trial population, semaglutide increased time to first HF events or CV death (HR: 0.73; 95% CI: 0.62-0.87; P = 0.0005), HF events alone (HR: 0.73; 95% CI: 0.58-0.92; P = 0.0068), and CV death alone (HR: 0.71; 95% CI: 0.56-0.89; P = 0.0036). The risk reduction for the composite HF outcome was similar in those with (HR: 0.73; 95% CI: 0.54-0.98; P = 0.0338) and without (HR: 0.72; 95% CI: 0.58-0.89; P = 0.0028) HF at baseline. The risk of HF outcomes (HF events or CV death) was generally higher in participants categorized as NYHA functional class III and those with the HF reduced ejection fraction subtype, regardless of treatment. Conclusions: Semaglutide substantially reduced the risk of time to first composite outcome of HF events or CV death, as well as HF events and CV death alone, in a high-risk population with T2D and CKD. These effects were consistent regardless of history of HF. (A Research Study To See How Semaglutide Works Compared to Placebo in People With Type 2 Diabetes and Chronic Kidney Disease [FLOW]; NCT03819153)
CRIS-Team Scopus Importer:2024-10-11
Keywords: chronic kidney disease; heart failure; outcomes; semaglutide; type 2 diabetes